Uzbekistan Investment Cooperation with the European Reconstruction and Development Bank - Saydaliyeva Lazizakhon (Zien Journals, 2023)
Uzbekistan's investment cooperation with the European Bank for Reconstruction and Development (EBRD) has been significant in promoting economic development and reforms in the country. This scientific and practical article is devoted to analyses of the investment cooperation between Uzbekistan and the European reconstruction and development bank.
Keywords: Economy; finance; macroeconomy; stabilizing the commercial banks